Трансмиссионная линия или лабиринт в акустических системах - Шелякин, О. И. (ХНУРЕ, 2012)
The given works is devoted to the design of acoustic Systems with transmission line or acoustic ≪labyrinth≫. If for a labyrinth it is possible with simplifications to execute the analysis and calculation, in regard to a transmission line - basic processes in them is not added to the analytical methods of analysis. Ail present information is based on practical researches
Keywords: лабиринт в акустических системах; трансмиссионная линия